1995
DOI: 10.1007/bf01931114
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity of the blood-feeding insectRhodnius prolixus increases in successive periods of egg production

Abstract: Abstract. The fecundity of the blood-feeding insect, Rhodnius prolixus, was observed to increase in successive periods of egg production, each period being triggered by a single large blood meal. As previously published, the fecundity of mated animals was significantly higher than that of unmated animals for the first period of egg production. For a second period of egg production, fecundity increased significantly in both mated and unmated animals. By the fourth period, fecundity had returned to first-feed va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…In NCCII-sectioned animals, the maximum number of eggs made and the E values reached did not differ significantly between mated and unmated animals. In control animals, the number of eggs made was significantly higher in mated animals compared to unmated animals, and the values reached were similar to those reported previously for Rhodnius reared this laboratory (see Chiang and Chiang, 1995). Compared to their respective controls, NCCII-sectioned mated animals increased egg production by approximately 24%, and NCCII-sectioned unmated animals, by approximately 100%.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In NCCII-sectioned animals, the maximum number of eggs made and the E values reached did not differ significantly between mated and unmated animals. In control animals, the number of eggs made was significantly higher in mated animals compared to unmated animals, and the values reached were similar to those reported previously for Rhodnius reared this laboratory (see Chiang and Chiang, 1995). Compared to their respective controls, NCCII-sectioned mated animals increased egg production by approximately 24%, and NCCII-sectioned unmated animals, by approximately 100%.…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, it is clear from the present study that inhibition imposed by the brain is considerable; the level of fecundity reached by NCCII-sectioned mated or unmated animals appears to be the maximum amount that can be obtained by this insect. Similar fecundity levels have been recorded following denervation of the CA in unmated (Davey et al, 1986) and mated (Davey, 1987) animals, but multiple feedings (Chiang and Chiang, 1995), which increase egg production without injury to the animal, failed to reach maximums recorded in the denervation studies.…”
Section: Discussionsupporting
confidence: 70%
“…A previous study showed that allowing unmated insects to feed on the belly of a rabbit more than once raised their fecundity levels to that of mated animals (Chiang and Chiang, 1995). To avoid the possibility that the act of feeding, in addition to the amount of blood ingested, affects fecundity, this study only includes those insects that fed at least 100 mg on their first attempt to feed.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, this double feeding does not mimic the natural setting, and the initial failed attempt could trigger autonomic processes that influence the insect's response to the second feeding attempt. For instance, unmated R. prolixus obtains fecundity levels of mated insects when fed more than once (Chiang and Chiang, 1995). Therefore, it is still not known whether the insect's ability to convert the ingested food into eggs is affected when offered a single blood meal through an artificial membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation